THE VALUE OF NON-TIMBER FOREST PRODUCTS (NTFPs) IN PROMOTING INDIA'S RURAL LIVELIHOODS - Sujoy Hazari; Mamoni Kalita; Biswajit Lahiri (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2023)
Non-timber forest products (NTFPs) are biological elements other than wood that is usually collected from forests for human and animal use and have both a consumptive and an exchange value. NTFPs provide a major contribution to the livelihood and health of the poor. The article aims to describe the present condition of NTFPs and marketing issues for NTFPs in India, as well as their importance in improving rural livelihoods. A systematic research review approach was used to get the desired results.The study retrieved approximately 238 articles from different databases and filtered 191, highlighting 51 articles related to the keywords, published between 1988 and 2022 were included in the analysis. During the investigation, forty one numbers of NTFPs were identified and documented and numerous potential NTFPs for enterprise growth have been identified according to the different zones of India. Rural people are using NTFPs for wide range of uses, including food, fodder, fibre, traditional medicine, domestic items, agricultural equipment, and construction materials, and many of them are linked to cultures. Promotion and domestication of NTFPs, as well as suitable policy frameworks for harvesting and better processing techniques, are all required for increased food security, poverty reduction, and improved livelihoods. Site-specific and species-specific strategies may be created for the preservation, management, and exploitation of NTFP resources.NTFPs play a significant role in improving rural livelihoods in India, as well as providing a valuable source of employment for rural residents though it has complex marketing system.